2004
DOI: 10.1016/j.precamres.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Bear River dykes (1265–1269 Ma): westward continuation of the Mackenzie dyke swarm into Yukon, Canada

Abstract: The 1.27 Ga Mackenzie dyke swarm, the largest on Earth, radiates from a point in the western Canadian Arctic and extends across much of the Canadian Shield. Possible western extensions of the swarm are largely obscured by younger sedimentary cover. Paleoproterozoic inliers in northern Yukon host the Bear River dykes (BRD), herein dated by U-Pb baddeleyite and zircon methods at 1268.5 ± 1.5 Ma and 1264.6 ± 1.2 Ma. The BRD share similar geochemical and Nd-isotopic characteristics with the Mackenzie dykes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…1318 Ma A-type granite and granitic porphyry in this contribution and the identification of a 1330± 11 Ma to 1313± 17 Ma granite pluton on the northern margin of NCC (Zhang et al, 2011) give felsic magmatic evidence to support an extensional event occurred in the northern NCC in the late Mesoproterozoic. These ages are similar to those in other regions such as Laurentia and Baltica (Anderson and Morrison, 2005;Emslie and Loveridge, 1992), Greenland (Upton et al, 2003), Africa (Mayer et al, 2004), and South America (Bettencourt et al, 1999), with coeval abundant mafic dike swarms (or sills) (Black et al, 1991;Ernst and Buchan, 2001;Ernst et al, 2000Ernst et al, , 2008LeCheminant and Heaman, 1989;Schwab et al, 2004;Upton et al, 2005;shown in Table 4) in these cratons, suggesting intraplate extension of the Columbia supercontinent Zhang et al, 2009;Zhao et al, 2002). The available paleomagnetic data from NCC Pei et al, 2006) show that the NCC shares similar paleomagnetic poles with Laurentia (Emslie et al, 1976;Halls and Heaman, 2000;Harlan and Geissman, 1998;Harlan et al, 1994), Siberia (Ernst et al, 2000), and Baltica Pesonen, et al, 2003) during late Paleoproterozoic to early Mesoproterozoic, indicating that these paleo-continents drifted together or close during this period (Fig.…”
Section: Tectonic Implicationssupporting
confidence: 77%
“…1318 Ma A-type granite and granitic porphyry in this contribution and the identification of a 1330± 11 Ma to 1313± 17 Ma granite pluton on the northern margin of NCC (Zhang et al, 2011) give felsic magmatic evidence to support an extensional event occurred in the northern NCC in the late Mesoproterozoic. These ages are similar to those in other regions such as Laurentia and Baltica (Anderson and Morrison, 2005;Emslie and Loveridge, 1992), Greenland (Upton et al, 2003), Africa (Mayer et al, 2004), and South America (Bettencourt et al, 1999), with coeval abundant mafic dike swarms (or sills) (Black et al, 1991;Ernst and Buchan, 2001;Ernst et al, 2000Ernst et al, , 2008LeCheminant and Heaman, 1989;Schwab et al, 2004;Upton et al, 2005;shown in Table 4) in these cratons, suggesting intraplate extension of the Columbia supercontinent Zhang et al, 2009;Zhao et al, 2002). The available paleomagnetic data from NCC Pei et al, 2006) show that the NCC shares similar paleomagnetic poles with Laurentia (Emslie et al, 1976;Halls and Heaman, 2000;Harlan and Geissman, 1998;Harlan et al, 1994), Siberia (Ernst et al, 2000), and Baltica Pesonen, et al, 2003) during late Paleoproterozoic to early Mesoproterozoic, indicating that these paleo-continents drifted together or close during this period (Fig.…”
Section: Tectonic Implicationssupporting
confidence: 77%
“…The ‡1.58 event may be linked to Racklan orogeny and subsequent c. 1.60 Ga voluminous hydrothermal brecciation . The 1.27-1.25 Ga ages are likely a reflection of the Bear River dyke emplacement, during the Mackenzie igneous event at c. 1.27 Ga (Schwab et al, 2004).…”
Section: Interpretation Of Zircon Agesmentioning
confidence: 93%
“…The 1.27–1.25 Ga ages are likely a reflection of the Bear River dyke emplacement, during the Mackenzie igneous event at c . 1.27 Ga (Schwab et al. , 2004).…”
Section: Interpretation Of Zircon Agesmentioning
confidence: 99%
“…6h;Fahrig 1987;Baragar et al 1996). An even greater fan angle (1508) is implied by the identification of coeval Bear River dykes in the Yukon (Schwab et al 2004). The coeval Coppermine Volcanics (up to 2 km thick) and other isolated volcanic rocks (e.g., the Tweed volcanics, Sevigny et al 1991) are the erosional remnants of originally much more widely distributed flood basalts.…”
Section: Ma: Northern Laurentiamentioning
confidence: 99%